Rancang Bangun Rangkaian Penggerak Motor Solar Tracker - I Wayan Sugara Yasa; I Made Asna; Catur Sumartdiono (Universitas Pendidikan Nasional, 2022)
A Solar Tracker is a device that directs the payload towards the sun. Solar panel charge, parabolic trough, Fresnel reflector, mirror or lens. For flat panel photovoltaic systems, tracers are used to minimize the angle of incidence between the incoming sunlight and the photovoltaic panels. This system increases the amount of energy generated from the fixed amount installed in the power generation capacity. Solar Cell or solar panels are electronic components that convert solar energy into electrical energy. Photovoltaic (PV) is a technology that functions to convert or convert solar radiation into electrical energy. each function as a store of electrical energy received by the solar cell. The solar tracker can follow the movement of sunlight from east to west and look for the strongest sunlight, and the design of this system can provide an efficiency value of 3% to 25% of solar panel electricity output in utilizing solar energy. By utilizing 4 Light Dependent Resistor (LDR) sensors, the maximum movement of the solar panels can move through 2 stepper motors connected to the solar tracker system.